A reference ontology for harmonizing process-reference models - César Jesús Pardo-Calvache; Félix Oscar García-Rubio; Francisco José Pino-Correa; Mario Piattini-Velthuis; Maria Teresa Baldassarre (Revista Facultad de Ingeniería Universidad de Antioquia, 2014)
For  a  couple  of  decades,  process  quality  has  been  considered  one  of  the  main  factors  in  the  delivery  of  high  quality  products.  Multiple  models  and  standards have emerged as a solution to this issue. However, for any company, the harmonization of diverse models with the aim at fulfilling its quality requirements is not an easy task to pursue. The difficulty fundamentally lies in the fact that there is a lack of specific guidelines, together with an evident inexistence of a homogeneous representation that could make the endeavour with  regards  to  Software  Engineering  less  intense.  In  order  to  address  this  challenge,  this  paper  presents  a  Ontology  of  Process-reference  Models,  called PrMO. It defines a Common Structure of Process Elements (CSPE) as a means to support the harmonization of structural differences of multiple reference  models,  through  the  homogenization  of  their  process  structures.  PrMO has been validated through instantiation of the information contained in different models, such as CMMI-(ACQ, DEV), ISO (9001, 27001, 27002, 20000-2),  ITIL,  COBIT,  Risk  IT,  Val  IT,  BASEL  II,  amongst  others.  Both  the common structure and the homogenization method are presented herein, along with an application example.